Crossroads of culture: anthropology collections at the Denver Museum of Nature & Science - Colwell-Chanthaphonh, Chip, author; Nash, Stephen E., author; Holen, Steven R., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2010)
The hectic front of the Denver Museum of Nature & Science hides an unseen back of the museum that is also bustling. Less than 1 percent of the museum's collections arc on display at any given time, and the Department of Anthropology alone cares for more than 50,000 objects from every corner of the globe not normally available to the public. This lavishly illustrated book presents and celebrates rarely seen baskets, jewelry, sculptures, clothing, and other highlights from the Denver Museum of Nature & Science's exceptional anthropology collections. The book presents 123 full-color images to highlight the Museum's cultural treasures. Selected for their individual beauty, historic value, and cultural meaning, these objects connect different places, times, and people. From the mammoth hunters of the Plains to the first American pioneer settlers to the flourishing Hispanic and Asian diasporas in downtown Denver, the Rocky Mountain region has been home to a breathtaking array of cultures. Many objects tell this story of the Rocky Mountains' fascinating and complex past, whereas others serve to bring enigmatic corners of the globe to modern-day Denver. Crossroads of Culture serves as a behind-the-scenes tour of the museum's anthropology collections. All the royalties from this publication will benefit the collections of the Denver Museum of Nature & Science's Department of Anthropology.--Book jacket.
One of the great institutions: an introduction -- American ethnology collection -- American archaeology collection -- World archaeology collection -- World ethnology collection -- "Never finished": the anthropology collections today and tomorrow.
Keywords: Ethnological museums and collections -- Colorado -- Denver